Cloning and characterization of rat 4.5S RNAI genes. - Takeuchi, Y (1986)
Genomic clones containing genes for 4.5S RNAI, which is an abundant small nuclear RNA found in rodent cells, were obtained from a rat genomic library. Thirty-four clones that formed RNase A resistant hybrids with 3'-end-labeled 4.5S RNAI were isolated, and seven of them (clones lambda I39, lambda I41, lambda I42, lambda I51, lambda I106, lambda I123 and lambda I154) were characterized by sequencing and in vitro transcription. Clones lambda I41 and lambda I123 carry one and two genes, respectively, with identical sequences to that of 4.5S RNAI and are actively transcribed in vitro. However, the other five clones contain sequences that seem to be pseudogenes for 4.5S RNAI, since they have nucleotide substitutions or deletions in the sequence corresponding to 4.5S RNAI or are not transcribed. Four clones (lambda I39, lambda I42, lambda I106 and lambda I154) were found to have 13-18 nucleotide-long direct repeats flanking the 4.5S RNAI sequences. The genomic organization of the genes and their related sequences is discussed.